El acompañamiento familiar en los adultos mayores para lograr el bienestar social del Centro Gerontológico Diurno de Loja, desde un enfoque Social. - Cordero Jiménez, Cristina Maribel (2025)
Given the importance of family support in older adults, the research focused on the study of: ̈Family support in older adults to achieve social welfare in the Gerontological Day Center of Loja, from a social approach ̈. The theoretical sections and bibliographical references have allowed me to explore the influence of family support in the lives of older adults, analyzing how this factor impacts their emotional and social well-being. The methodology used is purely exploratory, descriptive, it is a mixed research approach that combines quantitative and qualitative methods, through the use of research techniques such as unstructured interviews, survey and focus groups, which allowed me to fulfill my research objectives, the results obtained answered the scientific question What is the correct family support to achieve the social welfare of the older adult? in which a diminished participation of the family in the care of older adults was evidenced, often due to work obligations and time constraints. This lack of support can lead to feelings of sadness and isolation in older adults. The study concludes that it is necessary to foster the inclusion of older adults in family life and improve intergenerational communication. In addition, it suggests the implementation of awareness and support programs to strengthen the bond between older adults and their families, thus improving their quality of life and social well-being. This research paper highlights the importance of collaboration between families and institutions to provide a more supportive and effective care environment for older adults.